2010
DOI: 10.1021/op100031u
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids as Phase-Transfer Catalysts: Etherification Reaction of 1-Octanol with 1-Chlorobutane

Abstract: Various ionic liquids have been examined along with some traditional phase-transfer catalysts, such as Aliquat reagents, in a standard liquid−liquid phase-transfer catalysis (LLPTC) reaction. A standard O-alkylation LLPTC reaction was chosen because of its relatively high yields and low incident of reaction side products. As expected, quaternary tetraalkyl ammonium catalysts all resulted in high conversion to product. Aliquat HTA-1, a high temperature phase-transfer catalyst normally used in nonaqueous reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Recently, Firouzabadi and co-workers reported the etherification of different classes of alcohols using catalytic amounts of the heteropolyacid AlPW 12 O 40 . [18][19][20][21] Elegant catalytic methods for etherification reactions are represented by the use of transition metals. Reductive etherification from carbonyl compounds can be achieved using organosilanes and Lewis acid catalysts such as BiCl 3 [12] or FeCl 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Firouzabadi and co-workers reported the etherification of different classes of alcohols using catalytic amounts of the heteropolyacid AlPW 12 O 40 . [18][19][20][21] Elegant catalytic methods for etherification reactions are represented by the use of transition metals. Reductive etherification from carbonyl compounds can be achieved using organosilanes and Lewis acid catalysts such as BiCl 3 [12] or FeCl 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Some characteristics of these Brönsted acids brought our attention, for instance, their capacity to form hydrogen bonds with suitable Lewis bases 12 suggested that they should easily interact with glycerides and their derivatives. Also, the known ability of imidazol ionic liquids to serve as phase transfer agents 13 should be helpful to keep in contact the hard to mix substances of different polarities. These qualities prompted us to use the easily prepared Brönsted acidic 3-methylimidazolium hydrogensulfate as catalyst for a) the transesterification of sunflower oil, and b) the ketalisation of glycerol with acetone, two reactions which suffer from the poor solubility of triglycerides in methanol, and glycerol in acetone.…”
Section: Resultsmentioning
confidence: 99%
“…These qualities prompted us to use the easily prepared Brönsted acidic 3-methylimidazolium hydrogensulfate as catalyst for a) the transesterification of sunflower oil, and b) the ketalisation of glycerol with acetone, two reactions which suffer from the poor solubility of triglycerides in methanol, and glycerol in acetone. The known poor catalytic effect of imidazolium cations in etherification reactions 13 indicated that more drastic reaction conditions should be used, if the intended transesterification and ketalisation reactions were to be properly performed. Fortunately, we found that these extreme conditions resumed to methanol or acetone reflux temperatures, with reaction times up to 24 h, two factors that do not imparted the development of the combined processes.…”
Section: Resultsmentioning
confidence: 99%
“…Bender et al (2010) evaluated a series of ILs including Aliquat ® 336 as phase transfer catalysts for the etherification reaction of 1-octanol with 1-chlorobutane. The conversions ranged from 87-96% with Aliquat ® 336 catalysts.…”
Section: Applications As Catalysts and Solvents In Organic Synthesismentioning
confidence: 99%